Ethnobotany, volatile iols and secretion tissues of Werneria poposa from Argentina - Abella García, Luis (2000)
Folk medicines are gaining great importance as information sources on traditional medicinal plants. The aim of this paper is the study of a plant traditionally employed by the Puna inhabitants: Werneria poposa Phil. Morphology of its secretory tissue and other histological diagnostic features, as well as the chemical composition of its essential oil, is described. Puna inhabitants use W. poposa mainly as an infusion for mountain sickness ('soroche'), stomach and hepatic disorders and cold. It is also used externally as a hot bath or unguent for rheumatic pains or traumas. Secretory tissues are schizogenous ducts in leaves and stems. Thirty-one components were detected in the essential oil by means of GC/MS analysis. Oil was characterized by the presence of high content of β-pinene (21.7%), α-pinene (5.5%), terpinen-4-ol (5.3%), α-terpinene (5.2%), β-phellandrene + 1,8-cineole (4.8%), isopulegol (4.8%) and β-citronellal (4.6%). At the present time, W. poposa is consumed as a medicinal plant, mainly in the northwest of Argentina, not being commercialized in the urban centers.